Objective evaluation of clinical outcomes of laparoscopy-assisted pylorus-preserving gastrectomy for middle-third early gastric cancer - Xia, Xiang (BMC Cancer, 2019)
BACKGROUND: Laparoscopic-assisted pylorus-preserving gastrectomy (LAPPG) is a minimally invasive function-preserving surgery for early gastric cancer. This study was designed to investigate the clinical outcomes between LAPPG and laparoscopy-assisted distal gastrectomy (LADG) by objective evaluation. METHODS: A total 167 pT1N0M0 gastric cancer patients underwent LAPPG(n = 70) and LADG(n = 97) were retrospectively analyzed. By evaluating the functional advantages, objective short-term and one year follow-up outcomes were compared. RESULTS: There is no significant difference in perioperative clinical characteristics as well as pathologic results between LAPPG and LADG group while the cost is higher in latter(p = 0.004). The Clavien–Dindo grade II or higher complications were 15.7 and 13.4% in LAPPG and LADG group respectively(p = 0.824). In one year follow-up, nutritional status was significantly better in LAPPG group accompanied by better pylorus function preserving. CONCLUSION: LAPPG is an acceptable surgical procedure for pT1N0M0 middle portion gastric cancer patients in terms of nutritional and economic advantage. TRIAL REGISTRATION: Chinese Clinical Trial Registry (ChiCTR-PIC-17012358, Date of Registration:2017-08-14).